A method for weighted ranking of full tensor in situ stress test results - Musolino, M; Niedzielski, L; Wesseloo, J; Chester, C (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Accurate characterisation of the in situ stress field is essential for the design and operation of cave mines, where long-term stability and tactical controls depend on reliable stress inputs. However, early project stages often suffer from sparse and inconsistent stress data, complicating the development of representative sitewide stress models. This paper presents a pragmatic methodology for building confidence in stress measurements by a weighted ranking of full tensor in situ stress test results. The ranking is achieved by incorporation of overburden stress modelling from density block models and borehole breakout observations. The approach adapts Euclidean averaging techniques to produce a depth-dependent stress gradient tensor, with individual test results weighted based on alignment with vertical stress models, breakout orientations, and semi-qualitative test quality assessments. Application of this method to a dataset comprising overcoring, acoustic emission, and deformation rate analysis tests resulted in improved confidence in the site’s virgin stress field, including a 24° refinement in major principal stress orientation and magnitude adjustments of ±3 MPa. The proposed ranking system enhances the robustness of stress models used in mine planning and supports early-stage geotechnical decision-making in cave mining environments. Discussion surrounds considerations when applying the method to different mine sites and the opportunity to include other stress proxies, such as hydrofrack tests.
Keywords: in situ stress